FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PNEUMONIA PADA BALITA - Juniarti Asyari (JURNAL KEPERAWATAN, 2025)
Background: Pneumonia is a serious condition of the respiratory system caused by a bacterial/viral infection that attacks the small structures in the lungs that serve as air sacs, kno n as alveoli, often leading to the filling of pus and fluid in them, resulting in difficulty breathing and decreased oxygen levels in the body. Pneumonia is suite dangerous and can even cause death, hence the need to know the factors that cause pneumonia so that this disease can be prevented. Objective: The purpose of this study as to determine the factors associated with the incidence of pneumonia in toddlers in the Sakura room of Depati Hamzah Pangkal Pinang Hospital. Methods: The research design carried out in this study was quantitative research with cross-sectional methods. The population in this study was 117 mothers and a sample of 60 mothers who had toddlers who were treated in the Sakura Room at Depati Hamzah Hospital.  This research was conducted in the Sakura Room of Depati Hamzah Pangkalpinang Hospital. Results: Based on this study it can be seen that there is a significant relationship bet een exclusive breastfeeding (P = 0.000), there is a significant relationship bet een mother's education (P = 0.000), The association bet een exclusive breastfeeding, family members' smoking habits (p=0.000) and the incidence of pneumonia in toddlers in the Sakura Room of Depati Hamzah Pangkalpinang Hospital. Conclusion: The conclusion of this study is that there is an association between exclusive breastfeeding, mother's education, and family members' smoking habits with the incidence of pneumonia among toddlers in the Sakura Room of Depati Hamzah Pangkalpinang Hospital. Keywords: Hospital; Pneumonia; Toddlers